Descriptive Study of Knowledge About Leucorrhoea and Personal Hygiene Attitudes of Young Girls at Muhammadiyah 5 Junior High School Yogyakarta - Diana Diana; Wiwin Hindriyawati; Desi Ekawati (CV. Rayyan Dwi Bharata, 2023)
Vaginal discharge is still one of the main burdens of disease in developing countries and a classic problem for women. Many women in Indonesia do not know about vaginal discharge so they consider vaginal discharge as common and trivial. Based on BKKBN data, 45% of adolescent girls aged 15-24 years in Yogyakarta have experienced vaginal discharge (Shadine in Masyaroh, 2021). Adequate knowledge about vaginal discharge is very important so that they know how to deal with vaginal discharge. This study aims to determine the description of knowledge about vaginal discharge and Personal Hygiene attitudes in adolescent girls at SMP Muhammadiyah 5 Yogyakarta. This type of research is quantitative with descriptive design. The population of this study were adolescent girls at SMP Muhammadiyah 5 Yogyakarta, grades VII and VIII. The sample amounted to 116 people, the sampling technique in the study using accidental sampling. Data were collected using a questionnaire. Data analysis using univariate. The results showed the level of knowledge of adolescent girls about vaginal discharge with a good category of 84 people (72.4%), enough 26 people (22.4%), less 6 people (5.2%), and. Personal hygiene attitudes with good categories 21 people (18.1%) enough 93 people (80.2%), and less 2 people (1.7%), so it can be concluded that the picture of knowledge about vaginal discharge is dominated by good categories. While the attitude of adolescent girls about personal hygiene is dominated by enough.